Research on the Construction of Car Body Design Database and Intelligent Decision-Making Algorithm Model - Xince, Yu; Jixia, Wu; Jingxuan, Kang (2025 Asia-Europe Conference on Cybersecurity, Internet of Things and Soft Computing (CITSC), 2025)
This paper first structured the data and built a database covering various aspects of information such as body structure, material properties, and processing technology based on the diversity and complexity of body design. This supports the comprehensive analysis and optimization of design solutions. To improve the design efficiency and the rationality of the solution, this paper further proposed an algorithm model based on intelligent decision-making. Through multi-level feature extraction and adaptive learning, the model can generate the optimal body solution after inputting the design requirements. The simulation system verifies the accuracy and practicality of the algorithm model. The results show that the intelligent decision-making model shows high accuracy and reliability when dealing with complex body design solutions. At the same time, through the precise analysis of different simulation data, this paper finds that the systematic construction of the database and the intelligence of the algorithm model provide a strong guarantee for data support and decision optimization in the body design process. The research of this paper not only provides basic database support and intelligent decision-making tools for body design, but also provides an important reference for intelligent design and decision-making in other manufacturing fields.